Synthesis and antibacterial potential of novel thymol derivatives against methicillin-resistant Staphylococcus aureus and P. aeruginosa pathogenic bacteria - Shahi, Ashutosh; Manhas, Rakshit; Bhattacharya, Srija; Rathore, Arti; Kumar, Puneet; Samanta, Jayanta; Sharma, Manish Kumar; Mahapa, Avisek; Gupta, Prasoon; Anal, Jasha Momo H. (Frontiers in Chemistry, 2024)
The increasing threat of antibiotic resistance has created an urgent need for new antibacterial agents, particularly plant-based natural compounds and their derivatives.Thymol, a natural monoterpenoid phenolic compound derived from Monarda citriodora, is known for its aromatic and therapeutic properties, including antibacterial activity. This study focuses on synthesizing dihydropyrimidinone and dihydropyridine derivatives of thymol and exploring their antibacterial properties. The synthesized compounds were tested for their in vitro antibacterial potential against pathogenic microorganisms, specifically Pseudomonas aeruginosa (Gram-negative) and methicillin-resistant Staphylococcus aureus (MRSA) (Gram-positive). Among the synthesized derivatives, compound 3i ( Ethyl 4-(4-hydroxy-5isopropyl-2-methylphenyl)-2-imino-6-methyl-1,2,3,4-tetrahydropyrimidine-5-carboxylate) exhibited the most promising antibacterial activity, with minimum inhibitory concentration (MIC) values of 12.5 µM against P. aeruginosa and 50.0 µM against MRSA (Methicillin-Resistant Staphylococcus aureus). Additionally, compound 3i demonstrated a synergistic effect when combined with vancomycin, enhancing its antibacterial efficacy. The optimum